Adsorption kinetics and photocatalytic properties of Cu2ZnSnS4@porous g-C3N4 for contaminant removal. (1st November 2022) - Raza, Adil; Haidry, Azhar Ali; Shahzad, Muhammad Khuram; Hussain, Abdul Ahad; Azam, Ahmad; Saeed, Muhammad Shahzad; Ahsan, Muhammad
Abstract: Adsorption and photocatalytic degradation are widely recognized as the most important reaction pathways in water treatment from organic pollutants. It is desirable that the adsorption and photocatalytic properties are combined in the same catalyst used in the treatment. In this study, CZTS@Pg-C3 N4 (CZTS@PgCN) nanocomposite was synthesized by hydrothermal method and a series of experiments were carried out to determine the adsorption kinetics and photodegradation processes. Various models were used to interpret the experimental data to reveal the governing mechanisms. The adsorption kinetics of Rhodamine B (RhB) dye were agreed with the pseudo-second-order model (R 2 = 0.992). The obtained data corresponds to the Langmuir (R 2 = 0.993) and Fredundlich (R 2 = 0.937) isotherm models, and the maximum adsorption capacity of RhB is 7.26 mg/g. The Langmuir model is best fitted for adsorption experiment datasets examined in this study. Furthermore, the photodegradation rate of rhodamine B (RhB) dye over nanocomposite was evaluated and 90.4% of RhB degradation was obtained, which was considerably higher than PgCN and CZTS. After being recycled for four runs, the nanocomposite retained 75.3% of its original activity. Finally, an acceptable underlying mechanism for RhB degradation over CZTS@PgCN nanocomposite was proposed.